Prinsip 5S Pada Unit Kerja Kantor Produksi di PT Clariant Adsorbents Indonesia - Nurlela, Ella; Shalahuddin, Shalahuddin (JURNAL MAHASISWA BINA INSANI; Vol 8 No 2 (2023): Jurnal Mahasiswa Bina Insani (November 2023), 2023)
PT Clariant Adsorbents Indonesia is a branch factory in the chemical industry with its head office in Cileungsi, West Java. In the production office, the work tools are seen out of place so that the equipment cupboard looks dirty and cluttered with items that are not supposed to be. The lack of awareness of employees in the production department regarding the implementation of 5S (Seiri, Seiton, Seiso, Seiketsu, and Shitsuke) makes the production department unorganized and hinders work. The purpose of this research is to create a clean, comfortable and neat work environment so that it can increase employee effectiveness and productivity and improve employee performance. Analysis result, the achievement of 5S implementation in the production office at PT Clariant Adsorbents Indonesia can be seen that the implementation of 5S has not been maxiemized. The workroom floor is damaged, the dokumens that are actively used are not neatly arranged, the filing cabinets are not arranged based on index numbers and labels, and work tools are not in the right place. The lack of human resources in the production department makes communication related to 5S low because there are more jobs compared to the number of human resources. This is what causes the implementation of 5S to be unsustainable. Based on these problems, it is necessary to have an SOP (Standard Operating Procedure) regarding the implementation of 5S. SOP 5S has the goal that employees are responsible for implementing 5S so that the application of 5S principles can be carried out in a sustainable manner.